ANALISIS RISIKO FISIK PADA PETUGAS DI UNIT PENYIMPANAN REKAM MEDIS RUMAH SAKIT UMUM MADANI MEDAN - Andi Ritonga, Zulham; Karo-Karo, Siddik; Daeli, Cosmas Samuel; Partap, Joni (Akademi Perekam dan Informasi Kesehatan Imelda, 2025)
The medical record storage room is a place to store patient medical record files. Physical risk factors faced by officers include inappropriate lighting, uncomfortable temperatures, narrow distances between shelves, and room locations far from registration. This research is descriptive qualitative in nature and was conducted in the RSU Medical Records filling room. Madani Medan, aims to analyze these physical risk factors. Data was collected from four informants through interviews and observations, then analyzed qualitatively. The research results show that the lighting in the filling room is inadequate, especially in the corner of the room with closed windows and high ceilings, causing the lights to flicker frequently which interferes with comfort and work efficiency. Dim lights impact productivity and accuracy of file placement, and can trigger drowsiness. The room temperature was uncomfortable because the AC was broken and there were only two fans which did not cool the room enough, making the officers feel hot and sweaty. Each shelf about 60 cm apart was considered too narrow, hampering movement and slowing document retrieval, while the height reached 2.8 meters. Even though the room is spacious, its capacity is not sufficient to accommodate all the files, causing file accumulation. However, the distance between the registration room and medical record storage is quite close and does not hinder daily operations. This research recommends improvements and additions to adequate facilities to increase the comfort of medical record officers.